Estimation by a Sorption Technique of the Amorphous Contribution in the Phases Obtained during the Hydrothermal Crystallization of LTL-Type Zeolite - P.N. Joshi; T.H. Kim; K.I. Kim; V.P. Shiralkar (Adsorption Science & Technology)
Sorption techniques have been employed to estimate the amorphous contribution obtained during the progressive hydrothermal crystallization of the LTL phase from the K 2 O–Al 2 O 3 –SiO 2 –H 2 O system at 423 K. The curve showing the progressive depletion of the amorphous content as a function of the crystallization time exhibited an inverted sigmoidal-type shape indicative of distinct induction and crystallization stages. Samples with varying amorphous contributions were characterized by sorption uptake, XRD and chemical composition. The sorption uptake changes observed were found to be helpful in estimating the progress of the crystallization process. The influence of the amorphous contribution on the BET and Langmuir surface areas, and on the micropore void volume was examined using low-temperature nitrogen sorption methods. Estimation of the amorphous contribution by XRD has been compared with that estimated via sorption uptake using different probe molecules such as water, n-hexane, cyclohexane and benzene. The sorption uptake was found to be sensitive to the extent of amorphous content in the sample and to the characteristics of the probe sorbates. The sample with a 100% amorphous contribution as estimated by XRD methods exhibited lower values for this contribution when estimated by sorption techniques. The estimation of the amorphous contribution using benzene sorption data was found to be in excellent agreement with the amorphous contribution as estimated by XRD methods. A lower agreement was exhibited by the other sorbate probes studied.